Handbook of Flood Risk Management and Community Action : An International Perspective - Ahadzie, Divine Kwaku, editor 654872; Proverbs, David G., editor 366481; Soetanto, Robby, editor 366492; Oladokun, Victor Oluwasina, editor 654873; Taylor & Francis Group (Online service) 645650 (London, United Kingdom : Routledge, 2024)
"Recurring and worsening flood incidence around the world has necessitated the understanding and strengthening of community-based flood risk management from an international perspective. This handbook emphasizes the need for community action as part of an integrated flood risk management approach, highlighting case studies that have received recognition and made positive impacts, resulting in resilience-enhancing actions which can improve global community understanding. The content has been arranged such that it covers flood risk management approaches in the three main interfaces of: before, during and after the flood event. Experts writing on case studies from Africa, Oceania, Europe, Asia and the Americas come together to present lessons from regional and continental experiences that will be useful in providing an understanding of the nature and effectiveness of the human centred approach. The successful implementation of local and scientific knowledge as complimentary measures are also highlighted in a systematic review on the use of technologies for flood risk reduction. This interesting and diverse range of contributions seeks to showcase opportunities for cross-cultural knowledge transfer and uptake in the field of flood risk management. This handbook is essential reading for researchers, policy makers and leaders involved in flood and disaster management in the built environment, risk assessment, environmental and civil/construction engineering, and community action planning"--